A pilot study about infertile men's awareness of their reprotoxic exposures and the intervention of occupational medicine to assess them. Issue 1 (December 2016) - Christiaens, Amélie; Sari-Minodier, Irène; Tardieu, Sophie; Ianos, Oana; Adnot, Sébastien; Courbiere, Blandine; Perrin, Jeanne
Abstract Background Male infertility related to professional reprotoxic exposure has been assessed in several studies. Collaboration between occupational physicians and patients can yield information about the preventive measures that can be taken to avoid such exposure. The use of preventive measures is determined by the collaboration between reproductive medicine and occupational medicine and also by the patient's awareness of reprotoxic occupational exposures. Our andrology laboratory developed a systematic environmental interview that an occupational physician administers before semen analysis to assess patients' occupational reprotoxic chemical and physical exposures. This observational prospective study evaluated patients' feelings regarding this interview. The main outcome measure was the participants' score to determine their general reprotoxicant knowledge. The study also evaluated the patients' satisfaction about the interview with occupational physician and their attitude about reproductive toxicants. Results The mean score for general knowledge of reprotoxicants was 9.6 ± 2.7/16. The most frequently underestimated reprotoxic factor was excessive heat (34.7 % correct responses). In cases of semen parameter abnormalities AND recognized occupational reprotoxic exposure, 63.2 % of the patients said they would use individual protective devices, and 55.1 % said they would temporarily adapt their workstation. Regarding the interview with the laboratory's occupational physician, 80.7 % considered it moderately or very useful. Of the interviewed patients, 46.2 % reported having changed their living habits 2 months after the interview, and 88.5 % were satisfied or very satisfied with the care they received. All of the respondents said it would be useful to extend the interview to include their wives. Conclusions The data suggest that patients' knowledge about reprotoxic exposures can be improved, particularly knowledge related to physical exposure. The vast majority of patients were satisfied with the introduction of this new collaboration between reproductive and occupational medicine. Résumé Contexte Plusieurs études ont mis en évidence des infertilités masculines en lien avec une exposition reprotoxique professionnelle. L'interaction entre médecin du travail et patient peut faire émerger des informations sur les mesures preventives à mettre en place pour éviter ces expositions. L'utilisation de ces mesures préventives est déterminée par la collaboration entre médecin de la reproduction et médecin du travail et également par la conscience du patient de subir une exposition professionnelle reprotoxique. Notre laboratoire de spermiologie a mis en place un entretien systématique environnemental, assuré par un médecin du travail avant l'analyse de sperme, dans le but d'établir les expositions professionnelles reprotoxiques chimiques et physiques de chaque patient. Cette étude observationnelle prospective évalue la perception des patients de cet entretien. Le critère d'évaluation principal est le score de chaque patient évaluant ses connaissances générales sur les reprotoxiques. L'étude évalue également la satisfaction des patients à propos de cet entretien avec le médecin du travail et leur attitude vis à vis des reprotoxiques. Resultats Le score moyen de connaissances générales sur les reprotoxiques était de 9.6 ± 2.7/16. Le facteur reprotoxique le plus fréquemment sous estimé était la chaleur excessive (34.7 % de bonnes réponses). En cas d'altération des paramètres spermatiques associée à des expositions professionnelles reprotoxiques, 63.2 % des patients se disaient prêts à utiliser des dispositifs de protection individuelle, et 55.1 % à accepter une adaptation temporaire de leur poste de travail. Concernant l'entretien avec le médecin du travail du laboratoire de spermiologie, 80.7 % le considéraient modérément ou très utile. Parmi les participants, 46.2 % rapportaient un changement dans leurs habitudes de vie 2 mois après l'entretien, et 88.5 % étaient satisfaits ou très satisfaits des soins reçus. Tous les participants trouveraient utile d'étendre cet entretien à leur compagne. Conclusions Nos résultats suggèrent que les connaissances des patients sur les expositions reprotoxiques peuvent être améliorées, particulièrement en ce qui concerne les expositions physiques. La grande majorité des patients était satisfaite de l'introduction de cette nouvelle collaboration entre médecine de la reproduction et médecine du travail.